SOSIALISASI : LATAR BELAKANG, PROSES DAN TAKTIK - Ignatius Roni Setyawan (Bina Ekonomi, 2000)
This article will explain about the socialization of the organization. The first explanation is concerning with the motivation of the socialization process. These motivations are occupational stereotypes and ambiguous problem. Occupational stereotypes make different perception about organizational situation toward more applicants while ambiguous problem makes different importance and expectation between new comers with the old member. Thus, the presence of socialization is expected to reduce the occupation stereotypes and ambiguous problem by giving the real preview about in organization and the uniformity about expectation and importance between new comer and the organization.  By understanding the stage of the process and the tactics of socialization, it will be expected the organization could conduct the socialization process efficiently and effectively.